EKSPRESI KEBERAGAMAN DI LOKASI WISATA RELIGI PONPES TEBUIRENG JOMBANG - Bambang Haryanto (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2015)
This article aims at describing of pattern and social style at the religious tourism object at Ponpes Tebuireng (cottage) to explore the language fact in the social interaction. Furthermore, by exploring interaction here can give more understanding which is done by the society without blaming to their activities. This research is done based on Spradley theories (1997) entitle ethnography communication method. In addition, for data analysis using Sudaryanto theories